DOI: 10.23889/suthesis.48569
|View full text |Cite
|
Sign up to set email alerts
|

Creating and utilising the Wales Asthma Observatory to support health policy, health service planning and clinical research

Abstract: This thesis is the result of my own investigations, except where otherwise stated.Where correction services have been used, the extent and nature of the correction is clearly marked in a footnote(s). Other sources are acknowledged by footnotes giving explicit references. A bibliography is appended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 269 publications
(436 reference statements)
0
2
0
Order By: Relevance
“…I found that not all the studies provided an open link to the list of codes in their manuscripts, including: 1) the Clinical Risk Groups (CRGs) classification system, which may be because 3M CRGs has now been developed into a commercial product [180]; 2) the PMCA, which we wouldn't be able to find easily or straightforwardly (e.g., we searched by author names on different websites to locate the codes of the PMCA [191], which we located at this link: https://www.kpwashingtonresearch.org/our-research/our-scientists/rita-mangione-smith-mdmph/measurement-tools-research-dr-rita-mangione-smith; 3) and the paediatric complex chronic conditions (CCCs) classification system provided a non-open link in the related manuscript to the lists of codes [35]. This illustrates the difficulties that researchers have when attempting to locate some of the published algorithms with their codes.…”
Section: Specific Discussion Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…I found that not all the studies provided an open link to the list of codes in their manuscripts, including: 1) the Clinical Risk Groups (CRGs) classification system, which may be because 3M CRGs has now been developed into a commercial product [180]; 2) the PMCA, which we wouldn't be able to find easily or straightforwardly (e.g., we searched by author names on different websites to locate the codes of the PMCA [191], which we located at this link: https://www.kpwashingtonresearch.org/our-research/our-scientists/rita-mangione-smith-mdmph/measurement-tools-research-dr-rita-mangione-smith; 3) and the paediatric complex chronic conditions (CCCs) classification system provided a non-open link in the related manuscript to the lists of codes [35]. This illustrates the difficulties that researchers have when attempting to locate some of the published algorithms with their codes.…”
Section: Specific Discussion Pointsmentioning
confidence: 99%
“…He discovered high variation in the algorithms used to define asthma (n = 66 different algorithms) across 113 eligible articles. [191].…”
Section: Specific Discussion Pointsmentioning
confidence: 99%